A Cross‐Cultural Exploration of Perceptions of Altruism of Counselors‐in‐Training. Issue 2 (October 2015) - Limberg, Dodie; Ohrt, Jonathan H.; Barden, Sejal M.; Ha, Yo‐Sang; Hundley, Gulnora; Wood, Andrew W.
<x xml:space="preserve">Abstract</x> This study explored altruistic development as perceived by counselors‐in‐training from diverse cultures. Twenty‐two counselors‐in‐training from 4 countries participated in semistructured interviews about altruism. Using consensual qualitative research methodology, the authors identified 6 domains: biological, cognitive, social learning, religious/spiritual, counseling, and empathy. Findings and implications for counselor education are discussed.